Perícia criminal: uma abordagem de serviços - Rodrigues, Claudio Vilela (2010)
Value creation for society and gains in efficiency, efficacy and effectiveness has been reason of concerning in public sector. Based on a broad literature about service operations management, service value and public service value, this thesis has taken for granted that to know the value which a service must deliver to its main stakeholders is prior to organize it. According to literature, value might be created since designing public institutions until managing them. To integrate the different perspectives, it was used an approach that evaluates service value creation from the consequences on to its customers and the necessary resources to deliver them. These consequences were analyzed under four dimensions: utility, justice, solidarity, and aesthetic. Recourses analyzed were competences and technology. Thus, this thesis s purpose was to define the value of Forensic Science Service (FSS) to its main stakeholders. The specific objectives, which generated propositions, were: to find out the role played by FSS in its interorganizational network, to find out the main FSS characteristics, to identify critical factors for value delivery, and to propose some guides to design FSS. To achieve these objectives, a five-year qualitative, longitudinal and exploratory case study was carried out in a FSS federation unity. Subsidiary information was collected in six other FSS. Data also were collected from FSS stakeholders, using multiple methods. Results were analyzed and criticized based on theory. The findings showed that FSS takes part in a Public Safety and Criminal Justice interorganizational network and provide it with a service: the production of forensic evidence. FSS operations present exams variety, process variability, layout by fixed position in front office, and stakeholders diversity. FSS association with science highlights its intangibility. FSS utility dimension is to link the suspect to crime scene (or innocent someone wrongly accused) using science and technology, that is, it helps to build a narrative, in which defendants behaviors are trialed according to the law. There are obstacles on delivering this value dimension, like miscoordination among network members on crime scene preservation, for instance. The justice dimension assumes that every citizen must have access to FSS, independent of any pre-existing condition. Although, FSS hasn t been universalized yet. The solidarity dimension has a deeply conexion with Human Rights, both in avoiding constraining suspects during criminal investigations, and contributing to fair trials, in the sense that either prosecution or defense have access to the service in equal terms. However, FSS subordination to the Police jeopardizes its impartiality. The aesthetic dimension consists on helping Police solve crimes without constraining suspects. Besides the technical competence, FSS personnel need a communicational competence to a full client s knowledge. The technological resources are part of production process and critical for value delivery. Concluding, FSS should be redesigned as an independent agency in order to increase Criminal Justice impartiality. Finally, the study encourages reflections about the difficulties of applying service operations management concepts to a public organization that is changing, and it´s characterized by the diversity of stakeholders and by its fluid and poorly defined, although important value.